Kewenangan Penjabat Negeri Dalam Pengangkatan Dan Pemberhentian Saniri Negeri Laha Kaba Kecamatan Telutih Kabupaten Maluku Tengah - Koranelao, Abdul Latif; Nendissa, Renny Heronia; Soplanit, Miracle (Faculty of Law Universitas Pattimura, 2023)
State officials took arbitrary actions in appointing and dismissing Saniri without any deliberation from each clan or soa which had the right and authority to appoint and dismiss State Saniri Central Maluku Regency Regional Regulation No. 04 of 2006 concerning Guidelines for Structuring State Saniri/Village Consultative Bodies explains in Article 19 Point 1